#### Answer

y=-2x+17

#### Work Step by Step

m=$\frac{y_2-y_1}{x_2-x_1}$
m=$\frac{23-9}{-3-4}$
m=$\frac{14}{-7}$
m=-2
y-y$_1$=m(x-x$_1$)
y-9=-2(x-4)
y-9=-2x+8
y=-2x+17

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

y=-2x+17

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.